Perlindungan Hukum Pidana Atas Hak Pekerja Di PT. Medisafe Technologies (Studi di Dinas Ketenagakerjaan Kabupaten Deli Serdang) - Pangaribuan, Guntur; Lubis, Muhammad Salim Fauzi; Suniaprily, Firstnandiar Glica Aini; Maria, Juliya (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
One of the backgrounds to the birth of Law Number 13 of 2003 concerning Manpower is because several laws and regulations that have been in effect so far have placed workers in a less advantageous position in the service of manpower placement and the industrial relations system that emphasizes differences in position and interests so that they are considered no longer in accordance with current needs and future demands. The birth of Law Number 13 of 2003 concerning Manpower is expected to: Uphold the issue of protection and guarantees for workers; Implement various international instruments on ratified labor rights; As a member of the United Nations (UN) uphold and implement the Universal Declaration of Human Rights (HAM). Legal protection has been regulated in: The Preamble to the 1945 Constitution, namely based on Pancasila; The 1945 Constitution, namely Article 27 paragraph 2, Article 28 D paragraph 1, paragraph 2, Article 33 of Law Number 13 of 2003 concerning Manpower, and other regulations. Legally, the position of workers is free and balanced, but in practice it is often in an unbalanced state, causing problems. To overcome this, a solution is needed so that it can be accepted by all parties, is felt to be beneficial, has legal certainty and provides protection for all parties.